Photometric long-term variations and superhump occurrence in the Classical Nova RR Pictoris. Issue 2 (1st November 2017) - Fuentes-Morales, I; Vogt, N; Tappert, C; Schmidtobreick, L; Hambsch, F-J; Vučković, M
Abstract: We present an analysis of all available time-resolved photometry from the literature and new light curves obtained in 2013–2014 for the old nova RR Pictoris. The well-known hump light curve phased with the orbital period reveals significant variations over the last 42 yr in shape, amplitude and other details which apparently are caused by long-term variations in the disc structure. In addition, we found evidence for the presence of superhumps in 2007, with the same period ( ∼ 9 per cent longer than the orbital period), as reported earlier by other authors from observations in 2005. Possibly, superhumps arise quickly in RR Pic, but are sporadic events, because in all the other observing runs analysed no significant superhump signal was detected. We also determined an actual version of the Stolz–Schoembs relation between superhump period and orbital period, analysing separately dwarf novae, classical novae and nova-like stars, and conclude that this relation is of general validity for all superhumpers among the cataclysmic variables (CVs), in spite of small but significant differences among the sub-types mentioned above. We emphasize the importance of such a study in context with the still open question of the interrelation between the different sub-classes of CVs, crucial for our understanding of the long-term CV evolution.